Assessing the opportunities of landfill mining as a source of critical raw materials in Europe - Särkkä, Heikki; Kaartinen, T.; Hannus, Esa; Hirvonen, S.; Valjus, Tuire; Lerssi, J.; Dino, Giovanna Antonella; Rossetti, Piergiorgio; Griffiths, Zoe; Wagland, Stuart T.; Coulon, Frederic (Eurowaste, 2017)
Many of the metals in landfill constitute valuable and scarce natural resources. It has already been recognised that the recovery of these elements is critical for the sustainability of a number of industries. Arsenic (which is an essential part of the production of transistors and LEDs) is predicted to run out sometime in the next five to 50 years if consumption continues at the present rate. Nickel used for anything involving stainless steel and platinum group metals (PGMs) used in catalytic converters, fertilisers and others are also identified as critical materials (CM) to the EU economy at risk of depletion However, despite the increasing demand, none of this supply is supported by recycling. This is due to the high cost of recovery from low concentrations when compared to conventional mining. As demonstrated by the two pilot case studies of this study, mining landfill sites only for their metals content is not expected to be financially viable. However, other opportunities such as Waste-derived fuels from excavated materials exist which if combined , form the concept of ‘enhanced landfill mining’. have the potential to be highly energetic. The energy potential is comparable to the levels of energy of Refuse-Derived Fuels (RDF) produced from non-landfilled wastes.